Three-dimensional printing in medicine: Opportunities for development of optimal CT scanning protocols - Sun, Zhonghua; Aldosari, S. (Australasian Medical Journal Pty Ltd, 2018)
Three-dimensional (3D) printing has shown great promise with increased applications in the medical field. 3D printed models are reported to accurately replicate normal anatomy and pathology, assist pre-surgical planning and simulation, serve as a useful tool for medical education and improve patient-doctor communication. Another unique application of 3D printed realistic models is to develop optimal computed tomography (CT) scanning protocols for investigation of scanning parameters with low radiation dose while still achieving diagnostic images. This editorial highlights the application of using patient-specific 3D printed pulmonary artery model for investigation of optimal CT pulmonary angiography protocols for detection of pulmonary embolism.